Using social support for LGBTQ clients with mental illness to be out of the closet, in treatment, and in the community. Issue 3 (3rd July 2017) - Klein, Eileen
ABSTRACT: Lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) individuals are often faced with societal challenges that can lead to mental health or substance abuse issues. They may be misunderstood or mistreated when seeking services because of a lack of training in offering culturally sensitive treatment by service providers. A program, the Rainbow Heights Club, was developed to support LGBTQ individuals with a mental health diagnosis. All of the members are in treatment for their mental health and/or substance abuse problems, but prior to the development of the program did not have a place to feel accepted, supported, or have a sense of community. Members were surveyed determine if Rainbow Heights was helpful in maintaining themselves in the community. Results indicated that 75% of members are more consistent in following prescribed treatments, keeping them free from inpatient hospitalization, and 79% reported being clean and sober since coming to the Club.